Phytohormones involved in vascular cambium activity in woods: current progress and future challenges - Ding, Wenjing; Wang, Chencan; Mei, Man; Li, Xiaoxu; Zhang, Yuqian; Lin, Hongxia; Li, Yang; Ma, Zhiqiang; Han, Jianwei; Song, Xiaoxia; Wu, Minjie; Zheng, Caixia; et al. (Frontiers in Plant Science, 2024)
Vascular cambium is the continuation of meristem activity at the top of plants, which promotes lateral growth of plants. The vascular cambium evolved as an adaptation for secondary growth, initially in early seed plants, and became more refined in the evolution of gymnosperms and angiosperms. In angiosperms, it is crucial for plant growth and wood formation. The vascular cambium is regulated by a complex interplay of phytohormones, which are chemical messengers that coordinate various aspects of plant growth and development. This paper synthesizes the current knowledge on the regulatory effects of primary plant hormones and peptide signals on the development of the cambium in forest trees, and it outlines the current research status and future directions in this field. Understanding these regulatory mechanisms holds significant potential for enhancing our ability to manage and cultivate forest tree species in changing environmental conditions.